P139 CORRELATION OF CLINICAL REMISSION WITH MUCOSAL HEALING IN PEDIATRIC INFLAMMATORY BOWEL DISEASE. (18th January 2018) - Young, Denise; Mehta, Megha; Minich, Nori; Splawski, Judy; Sferra, Thomas J; Moses, Jonathan
Abstract: Background: IBD therapeutic endpoints have evolved over time with the addition of mucosal healing (MH) as a treatment goal. Adult data suggest patients who achieve MH have improved outcomes but pediatric data is lacking. The aims of our study was to evaluate the rate of MH, to correlate MH with clinical remission and identify medications associated with MH. Methods: This was a retrospective study of pediatric IBD patients seen from 2005–2015 with Crohn's disease (CD) or ulcerative colitis (UC) and had two or more endoscopies. Clinical activity was scored with weighted Pediatric Crohn's Disease Activity Index (wPCDAI) or Pediatric Ulcerative Colitis Activity Index (PUCAI) and Physician Global Assessment (PGA). Endoscopic images were blinded and independently reviewed by two staff physicians (TJS, JM). Analysis was done using Generalized Estimating Equations. Results: 52 patients with CD and 24 with UC were included in the analysis. Each had 1–3 repeat endoscopies for a total of 105 scopes. There was an equal number of males and females; 81% were Caucasian. There was excellent agreement between reviewers (ƙ = 0.919, p < 0.001). Overall rate of MH was 54%. MH was not associated with clinical remission by wPCDAI/PUCAI or PGA. The positive predictive value of wPCDAI/PUCAI or PGA in identifying patients with MH was 50%. There was an association between medication and PGA score (p = 0.009) but not with wPCDAI/PUCAI (p = 0.091). CD patients on biologics compared to mesalamine or immunomodulators had higher odds of clinical remission based on PGA. The association between medication and MH was not significant (p = 0.70). Conclusion: Our results indicate clinical assessment with wPCDAI, PUCAI or PGA are likely not reliable means of identifying MH. Biologics were associated with clinical remission but not MH; however, the study is underpowered due to small sample size. Further studies are needed to assess MH and determine optimal medical management of pediatric IBD patients.